PMEPA1 interference activates PTEN/PI3K/AKT, thereby inhibiting the proliferation, invasion and migration of pancreatic cancer cells and enhancing the sensitivity to gemcitabine and cisplatin. Issue 1 (30th June 2021) - Yang, Yang; Cheng, Tao; Xie, Peng; Wang, Lishan; Chen, Hong; Cheng, Zhangjun; Zhou, Jiahua
Abstract: To explore the biological activity of transmembrane prostateandrogen induced RNA (PMEPA1) in human pancreatic cancer (hPAC) cells and its drug sensitivity to gemcitabine (GEM) and cisplatin (DDP). Gene Expression Profiling Interactive Analysis (GEPIA) and Cancer Cell Line Encyclopedia (CCLE) were consulted to indicate the expression of PMEPA1 in hPAC tissues and cells. Quantitative real‐time PCR (RT‐qPCR) and western blot were performed to verify the indication. RT‐qPCR and western blot also detected the expressions of PTEN/PI3K/AKT before and after transfection of PMEPA1 siRNA plasmids. Cell counting Kit‐8 (CCK‐8) and EdU staining were performed to examine cell proliferation before and after transfection of phosphatase and tensin homologue delet2ed on chromosome ten (PTEN) siRNA plasmids. Transwell and wound healing detected the invasion and migration of hPAC cells. The expressions of MMP‐2 and MMP‐9 were detected by western blot. After GEM or DDP treatment, cell viability was observed by commercial kits and cell apoptosis by flow cytometry. GEPIA and CCLE predicted increased expression of PMEPA1 in hPAC tissues and cells, which was confirmed by quantitative reverse transcription polymerase chain reaction (RT‐qPCR) and western blot. PMEPA1 was also shown to be associated with disease‐free survival. Transfection of PMEPA1 siRNA plasmids affected the expressions of PTEN/PI3K/AKT. PMEPA1 interference inhibited the proliferation, invasion and migration of hPAC cells. Furthermore, PMEPA1 interference also enhanced the sensitivity of hPAC cells to GEM and DDP via PTEN interference. PMEPA1 interference inhibits the proliferation, invasion and migration of pancreatic cancer cells and enhances the sensitivity to GEM and cisplatin by activating PTEN/PI3K/AKT signaling.